Governance to enable climate resilient development of healthcare systems - A conceptual overview - Sophie Robinson; Glenn Hoetker; Kathryn Bowen (Elsevier, 2024)
Climate resilient development (CRD) is a future-focused solutions framework encapsulating climate adaptation and mitigation activities. It aims to prevent and prepare for the worst impacts of climate change whilst supporting sustainable development. When considering sustainability in healthcare systems, CRD goes beyond the current narrow focus on adaptation and mitigation to a more productive and integrated focus on how healthcare systems must equitably develop and transform to preserve the interconnected health of human and natural systems.The field of governance has received insufficient attention as a key determinant of CRD in healthcare systems, despite being a crucial enabling condition. It is through governance that climate resilient development policies are created, supported, implemented, and monitored. In this perspective we share a review that found no papers concerning how governance can enable CRD of healthcare systems followed by a broadened search which revealed a growing focus on elements of CRD (climate adaptation and mitigation) and barriers to climate adaptation and mitigation in healthcare systems.To respond to this gap, this perspective suggests there is value in jointly considering healthcare systems, climate resilient development and governance. We argue that transdisciplinary research combining these topics could provide practical and novel guidance for stakeholders involved in the pursuit of CRD of healthcare systems and could strengthen policy responses and actions.